PERAN KEPEMIMPINAN TRANSFORMASIONAL DALAM MEMBANGUN SINERGI TIM GURU MENUJU MADRASAH UNGGUL (STUDI KASUS DI MTS AL MUJAHIDIN 2 SAMARINDA) - Nisa, Rahmatiana Azizatun; Bahrani, Bahrani; Madzkuri, Muhammad Redza (STKIP Pesisir Selatan, 2025)
The role of transformational leadership in building teacher team synergy as a strategy towards a superior madrasah at MTs Al Mujahidin 2 Samarinda. Leadership in this madrasah is interesting because of the collective efforts to create a collaborative culture amidst the challenges of educational change and increasing demands for quality. This study uses a qualitative approach with a case study type, involving the madrasah principal and teachers as key informants through interviews, observations, and documentation. The madrasah principal consistently applies the four dimensions of transformational leadership: ideal influence, motivation, intellectual stimulation, and individual attention. Strategies such as regular forums, teacher involvement in decision making, and internal training are key to building solid team synergy. Challenges in administrative burdens and resistance to change, the madrasah principal is able to manage obstacles through an adaptive and relational approach. Transformational leadership not only increases individual motivation and performance, but is also able to engineer a collaborative, reflective, and progressive organizational culture. The novelty of this study lies in the application of transformational leadership in a madrasah based on Islamic values ​​and this leadership style forms teacher synergy as the main foundation towards a superior madrasah.